Single-cell sequencing reveals the cell map and transcriptional network of sporadic vestibular schwannoma - Yidian, Chu; Chen, Lin; Hongxia, Deng; Yanguo, Li; Zhisen, Shen (Frontiers in Molecular Neuroscience, 2022)
In this study, based on three tumor samples obtained from patients with sporadic vestibular schwannoma, 32,011 cells were obtained by single-cell transcriptome sequencing, and 22,309 high-quality cells were obtained after quality control and double cells removal. Then, 18 cell clusters were obtained after cluster analysis, and each cluster was annotated as six types of cells. Afterwards, an in-depth analysis was conducted based on the defined six cell clusters, including characterizing the functional characteristics of each cell subtype, describing the cell development and differentiation pathway, exploring the interaction between cells, and analyzing the transcriptional regulatory network within the clusters. Based on these four dimensions, various types of cells in sporadic vestibular schwannoma tumor tissues were described in detail. For the first time, we expanded on the functional state of cell clusters that have been reported and described Schwann cells in the peripheral nervous system, which have not been reported in previous studies. Combined with the data of sporadic vestibular schwannoma and normal tissues in the GEO database, the candidate biomarkers of sporadic vestibular schwannoma were explored. Overall, this study described the single-cell map of sporadic vestibular schwannoma for the first time, revealing the functional state and development trajectory of different cell types. Combined with the analysis of data in the GEO database and immunohistochemical verification, it was concluded that HLA-DPB1 and VSIG4 may be candidate biomarkers and potential therapeutic targets for patients with sporadic vestibular schwannoma.